Pengaruh Profesionalisme dan Etika Profesi Terhadap Pertimbangan Tingkat Materialitas Dalam laporan Keuangan: Study Kasus Kantor Akuntan Publik Provinsi Yogyakarta dan Jateng - Heryani Siti Nudyah (Magister Akuntansi FB-UK.Maranatha, 2021)
ABSTRACT This study aims to determine how the influence of professionalism and professional ethics on the consideration of the level of materiality in financial statements in public accounting firms, especially in the provinces of Yogyakarta and Central Java. This research is a survey research conducted on auditors who work in public accounting firms with a sampling technique by distributing questionnaires both in person and online. The number of questionnaires processed was 40 questionnaires, with details of 20 questionnaires from google form and 20 questionnaires from questionnaires. Data were analyzed using multiple linear regression analysis. The data used in this study used primary data obtained from the questionnaire method given directly to the auditors of public accounting firms in Yogyakarta and also Central Java, namely Surakarta and Semarang. The results of the study show that Professionalism and Professional Ethics affect the consideration of the level of materiality in the financial statements Keywords: professionalism, professional ethics, materiality level considerations